Work and Environment Related Characteristics Associated with Voice Disorders among Primary School Teachers - Herath, Maaheshi Deepika; Senarath, Upul; Suraweera, Inoka (Asian Journal of Interdisciplinary Research, 2024)
The objective of this study is to assess work and environment related factors associated with voice disorders among primary school teachers in the Colombo district in Sri Lanka. Methods: An institution based cross sectional study was conducted among 790 primary school teachers, in the Colombo District in Sri Lanka. They were selected by a stratified random sampling method. The validated Voice Handicap Index (VHI-30) questionnaire and a self-administered questionnaire were used for data collection. Sound levels within 10 selected classrooms were measured objectively using CR:303 sound level meter (Cirrus). Data analysis was by bivariate method with chi squared and logistic regression. Results: Among the work related characteristics assessed teaching 5 or more subjects (OR=1.40, CI = 1.039, 2.90), staying after school hours (OR=1.69, CI = 1.19, 2.38) were significantly associated with voice disorders. Among the factors associated with work environment, teachers having a speech pattern in yelling and shouting category (OR=2.25, CI=1.68, 2.99), speaking in noisy environments (OR=1.09, CI= 1.15, 3.15), being exposed to smoky dusty environments (OR = 1.61, CI= 1.19, 2.16), having average or high dust levels in classrooms (OR=2.03, OR=1.50, 2.76), having a moderate to high noise level in classrooms (OR= 1.93, CI=1.45, 2.58) and having ‘just adequate, inadequate and average’ space in a classroom (OR=1.74, CI=1.29, 2.34) were significantly associated with voice disorders. The sound levels objectively measured in classrooms revealed that all classrooms had higher than acceptable noise levels during a teaching session. Conclusions and recommendations: The association of voice disorders with work related characteristics were similar to the findings in other studies. However, the high noise levels detected in the classrooms on objective measurement were high. It is recommended that these findings be addressed through a multidisciplinary approach and National standards for acceptable noise levels within classrooms be established.